A Igreja que sonhamos construir - Libânio, João B. (Revista eclesiástica brasileira, 2005)
A new Pontificate is a most favorable occasion to dream of a Church we want to build upon the heritage of Vatican II’s and Medellín. From Vatican II, we should cherish and enrich a theology based on the hermeneutic paradigm. From it comes the Church image where God’s Word excels. It appears in a plurality of experiences, participative, collegial, comprehensive. Other features to be reinforced: universal vocation to sanctity, ecumenical and inter-religious dialogue as well as interection with the modern world, valuing religious freedom. The Medellín heritage left an indelible mark: the option for the poor in the Liberation Church. To prolong it means to take a prophetic-critic dimension, a Church of CEBs (basic ecclesiastic communities) with uncultivated liturgy, practising new ecclesiastical structures. A glance into the future demands a Church that faces the challenges of the current world: the ideology of an advanced modern and globalized society, the linguistic mixture, the religious phenomenon. The answers open ways towards a courageous resuming of the liberation practice, giving a new dimension to the official education and ecclesiastical hierarchy, the evangelization of cultures, and the surge of spiritualist religions. In a society of knowledge, it’s up to the Church to collaborate in the creation of a new ecological paradigm, and of an alternative project of society.